2019
DOI: 10.1044/2018_ajslp-18-0184
|View full text |Cite
|
Sign up to set email alerts
|

Helping Patients With Head and Neck Cancer Understand Dysphagia: Exploring the Use of Video-Animation

Abstract: Purpose Patients newly diagnosed with head and neck cancer should be informed of the ramifications of cancer treatment on swallowing function during their pretreatment consultation. The purpose of this study was to explore (a) the usefulness and (b) the acceptability of video-animation in helping patients to understand the basics of the swallowing mechanism and dysphagia. Method Thirteen patients treated for head and neck cancer participated in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
(31 reference statements)
0
21
0
4
Order By: Relevance
“…The use of animation media during the teaching process attracted students' interests so that they could easily understand the mechanism of the circulatory process. Research by Govender et al (2019) point out that education with animated videos is acceptable, interesting, informative and relevant for most cancer patients. Therefore, animated video is not only useful as an educational medium but also has the potential to infl uence the desire of patients to do preventive interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The use of animation media during the teaching process attracted students' interests so that they could easily understand the mechanism of the circulatory process. Research by Govender et al (2019) point out that education with animated videos is acceptable, interesting, informative and relevant for most cancer patients. Therefore, animated video is not only useful as an educational medium but also has the potential to infl uence the desire of patients to do preventive interventions.…”
Section: Resultsmentioning
confidence: 99%
“…As part of SIP SMART, patients underwent an x-ray swallow assessment that enabled a physiological analysis of swallowing and the selection of specific and targeted exercises. Patients were shown a video-animation of swallowing to anchor the pretreatment discussion, making it more concrete for the patient and promoting an interactive approach [10]. Specific behaviour change techniques such as goal setting, self-monitoring, and behavioural practice were actively employed.…”
Section: Intervention Groupmentioning
confidence: 99%
“…We have developed a new pre-treatment intervention (SIP SMART: Swallowing Intervention Package-Self Monitoring, Assessment, Rehabilitation Training), designed to address some of the shortcomings of previous clinical trials. The intervention development was informed by a series of studies including: a systematic review to identify behavioural strategies that could potentially promote patient adherence to swallowing exercises [8]; an in-depth interview study to establish patient reported barriers and facilitators to exercise adherence [9]; and a think-aloud study to explore the potential use of video-animation to improve how information about swallowing and dysphagia is conveyed to patients [10]. Further detail about the systematic development of SIP SMART using the Medical Research Council framework for the development and evaluation of complex interventions [11] and the Behaviour Change Wheel [12] is described elsewhere [intervention development manuscript under review].…”
Section: Introductionmentioning
confidence: 99%
“…Patients were shown a video-animation of swallowing to anchor the pre-treatment discussion, making it more concrete for the patient and promoting an interactive approach (10). Specific behaviour change techniques such as goal setting, self-monitoring, and behavioural practice were actively employed.…”
Section: Interventions and Proceduresmentioning
confidence: 99%